Payment received according to compositional and hygienic quality of raw milk in the Huaura Valley, Peru - Chagray A., Néstor (2023)
In Peru, the payment received by the producer per kilogram of raw milk is based on a base price, to which bonuses are applied according to quality criteria established by the dairy industry. In the present study, the relationship of compositional and hygienic quality with the value of payment per kilogram of milk in a dairy in the Huaura Valley was evaluated. Retrospective information on the total solids content (%ST), mesophilic aerobic count (UFC/ml) and the payment received (Peruvian sol - S/) per kilogram of raw milk (VP) was obtained from biweekly reports for the period 2017-2020. Data were analysed using Spearman’s trend and correlation analysis. The results showed a positive trend for the %ST (from 12.02% in 2017 to 12.21% in 2020) and negative for the CFU/ml (32,690 in 2017 to 18,117 in 2020). The PV had a similar trend to the %ST (S/ 1.39 in 2017 to S/ 1.41 in 2020). The %ST and VP had a seasonal behaviour, with falls in summer and in some winter months. The correlations between the VP with the %ST and VP with the CFU/ml had values of 0.88 (p<0.0001) and -0.21 (p>0.05); respectively. It is concluded that dairy farms should consider the positive relationship and seasonality of the %ST and VP and decrease the CFU/ml count so as not to exceed the values allowed by the industry to avoid discounts and achieve better payment values.